The Effect of Horn Beetle Nanochitosan (Xylotrupes gideon) Addition on The Hardness of Glass-ionomer Cement - Florencia Livia Kurniawan; Rosalina Tjandrawinata; Carolina Marpaung; Deviyanti Pratiwi; Komariah Komariah (Indonesian Dental Association, 2022)
Introduction: Glass ionomer cement (GIC) is a tooth-colored restorative material that is often used by clinical practitioners because it can release fluoride, is easy to apply to teeth and has minimal preparation techniques. The erosion and moisture-sensitive nature of GIC becomes a problem for a long-lasting aesthetic restoration. Therefore, modifications were made to improve its mechanical properties by adding nanochitosan (NCH) from horn beetle (Xylotrupes gideon). Objective: This study aimed to evaluate the effect of adding horn beetle nanochitosan to GIC liquid on the surface hardness and compared with conventional GIC. Methods: Forty cylindrical samples of GIC (GC Fuji® IX Extra, Tokyo-Japan, Lot 1912201) with a diameter of 4 mm and a thickness of 6 mm were divided into 4 groups, namely the GIC control group, GIC modified with 0.5wt%, 1wt%, 2 wt% nanochitosan. Each sample was immersed in artificial saliva for 24 hours and 7 days. Surface hardness before and after immersion was tested using a Vickers Microhardness tester (Shimadzu, Japan). The data were analyzed using the Kruskal Wallis test to determine the effect of horn beetle nanochitosan addition and the Wilcoxon Signed-Ranked test to determine the effect of immersion time on GIC surface hardness. Results: The Kruskal Wallis statistical test showed significant difference (p<0.05) between the control group and the 24 hours treatment group with the addition of 2wt% nanochitosan, which was the highest surface hardness value (133.1 ± 49.0 HV), followed by 1wt% (127.4 ± 25.5 HV) and 0.5wt% (117.7 ± 22.5 HV). The Wilcoxon Signed-Ranked test statistic also showed a significant difference (p<0.05) between the 24-hour and 7-day immersion time with the surface hardness value at 24 hours immersion greater than 7 days. Conclusion: The addition of 0.5wt%, 1wt% and 2wt% horn beetle nanochitosan can increase the GIC surface hardness value. ABSTRAK Pendahuluan: Glass ionomer cement (GIC) merupakan bahan restorasi sewarna gigi yang sering digunakan oleh praktisi klinis karena dapat melepaskan fluor, mudah diaplikasikan pada gigi, dan memiliki teknik preparasi yang minimal. Erosi dan sifat sensitif kelembaban dari GIC menjadi masalah untuk restorasi estetika yang tahan lama. Oleh karena itu, dilakukan modifikasi untuk meningkatkan sifat mekaniknya dengan menambahkan nanokitosan (NCH) dari kumbang tanduk (Xylotrupes gideon). Tujuan: Penelitian ini bertujuan untuk mengevaluasi pengaruh penambahan nanokitosan kumbang tanduk ke dalam cairan GIC terhadap kekerasan permukaan dan dibandingkan dengan Semen Ionomer Kaca (SIK) konvensional. Metode: Empat puluh sampel silinder GIC (GC Fuji® IX Extra, Tokyo-Japan, Lot 1912201) dengan diameter 4 mm dan ketebalan 6 mm dibagi menjadi 4 kelompok, yaitu kelompok kontrol GIC, GIC dimodifikasi dengan nanokitosan 0,5wt%, 1 wt%, 2wt%. Setiap sampel direndam dalam saliva buatan selama 24 jam dan 7 hari. Kekerasan permukaan sebelum dan sesudah perendaman diuji menggunakan Vickers Microhardness tester. Data dianalisis menggunakan uji Kruskal Wallis untuk mengetahui pengaruh penambahan nanokitosan kumbang tanduk dan uji Wilcoxon Signed-Ranked untuk mengetahui pengaruh waktu perendaman terhadap kekerasan permukaan GIC. Hasil: Uji statistik Kruskal Wallis menunjukkan perbedaan bermakna (p<0,05) antara kelompok kontrol dan kelompok perlakuan perendaman 24 jam dengan penambahan nanokitosan 2wt% yang merupakan nilai kekerasan permukaan tertinggi (133,1 ± 49,0 HV), diikuti sebesar 1wt% (127,4 ± 25,5 HV) dan 0,5% (117,7 ± 22,5 HV). Statistik uji Wilcoxon Signed-Ranked juga menunjukkan perbedaan yang nyata (p<0,05) antara lama perendaman 24 jam dan 7 hari dengan nilai kekerasan permukaan pada perendaman 24 jam lebih besar dari 7 hari. Kesimpulan: Penambahan nanokitosan kumbang tanduk 0,5wt%, 1% , dan 2wt% dapat meningkatkan nilai kekerasan permukaan GIC.